Hazardous And Toxic Waste (B3) Standard Design for Temporary Storage for Oil and Gas - Rachman, Lindra Aulia; Satriawan, Irfan; Pramono, Dwiyoso (Proceeding Mercu Buana Conference on Industrial Engineering, 2022)
One of the main activities in the oil and gas industry is the maintenance of diesel engines. There is a special process called preventive maintenance with regular oil changes. The process of changing oil is done regularly which results in B3 waste in the form of waste oil. Considering these aspects, the purpose of this research is to identify the temporary storage of petroleum waste for oil and gas based on the literature and the design of the B3 Temporary Waste Storage (TWS). The method used is descriptive qualitative methodology. The data refers to government regulations that have been made in order to create a safe, solicitous and orderly life. The results of these calculations are used as a reference in the design of the TWS, where the maximum waste capacity for the B3 Solid Waste Warehouse is 4.000 tons and for the B3 Liquid Waste Warehouse is 4.000 liters, and the building area of the B3 waste TWS is 108 m2. The layout design for new B3 waste is done based on suitability of characteristics B3 waste with a suitable building design (may combined in placing packaging waste).